A Critical Review of Common Methodological Approaches in Environmental Sustainability Practices within the Hotel Sector: In Pursuit of a Befitting Synthesis. - Khonje, Lameck Zetu; Simatele, Mulala Danny; Musavengane, Regis (Texas A and M University, 2021)
This paper uses a qualitative meta-synthesis approach and suggests an appropriate methodological approach to study environmental sustainability practices in the hotel sector in Malawi. Twenty selected articles published between 2007 and 2017 were purposefully selected for a meta-synthesis because of their scope. The results from this meta-synthesis indicate that the majority of researchers from developed countries use a quantitative method to establish the status of environmental sustainability practices in the hotel sector. The results also revealed that some researchers from developing countries used both quantitative and qualitative (mixed method) methods, whilst others preferred the use of qualitative. This paper, therefore, proposes a seven-stage version of the Grounded Theory methodology for studying environmental sustainability practices in the hotel sector in Malawi and Sub – Saharan Africa at large.